Adultery in the Novel Contract and Transgression - Tanner, Tony (Johns Hopkins University Press, 2020)
Originally published in 1979. Adultery is a dominant feature in chivalric literature; it becomes a major concern in Shakespeare's last plays; and it forms the central plot of novels from Anna Karenina to Couples. Tony Tanner proposes that transgressions of the marriage contract take on a special significance in the "bourgeois novels" of the eighteenth and nineteenth centuries. His interpretation begins with the general topic of adultery in literature and then zeroes in on three works-Rousseau's La Nouvelle Héloïse, Goethe's Die Wahlverwandtschaften, and Flaubert's Madame Bovary. His interpretation encompasses the role of women, the structure of the family, social mores, and the history of sexuality.